La comprensión de las organizaciones empresariales y su ambiente como sistemas de complejidad creciente: rasgos e implicaciones - Bohórquez, Luz Esperanza (Ingeniería, 2016)
Context: As a consequence of the increasing complexity of both, business organizations and the environment in which they operate, the current dominant trend of thought for understanding organizations is becoming insufficient to respond to changing conditions, and simultaneously generate slowness, in- flexibility, and fragility in decision-making, as well as negative externalities both in the environment and in society. An alternative trend of thought with foundation in the sciences of complexity suggests that adaptation via self-organiza- tion can solve such difficulties. Method: In the document the characteristics of the systems of increasing complexity are reviewed and elements that explain their capacity for self-organization are identified. On the basis of such review, the implications of understanding organisations as systems of increasing complexity are analyzed and articulated with recent research in organizational engineering and management that seek to increase the adaptability of the system. Results: A reflection is made regarding the implications for organizational engineering about designing business organizations, with increased ability to self-organize and more broadly to benefit from the growing complexity of the environment. Conclusions: Understanding business organizations as systems of increasing complexity offers a perspective notoriously different to the traditional paradigm which have been characterized by the reductionist approach. To this day the research on this is in its early stages, and there are no models and/or empirical evidence to corroborate broadly and completely the strength of these ideas. However, high levels of agility, flexibility and robustness that exhibit self-organized systems suggest considering interesting research questions regarding the design of flexible organizational structures, forms of governance, decisions-making in the absence of central control systems etc